Synthesis of Strong Cation Exchange Macroporous Polymer Cluster for Convective Protein Chromatography. Issue 10 (14th August 2019) - Lorenz, Marcel; Vogg, Sebastian; Finkelstein, Patrick; Storti, Giuseppe; Morbidelli, Massimo
Abstract: Alkyne‐terminated polyelectrolytic brushes based on 3‐sulfopropyl methacrylate are synthesized by reversible addition‐fragmentation chain transfer polymerization and subsequently linked to macroporous polymeric microclusters by Cu(I)‐catalyzed azide alkyne cycloaddition. It is shown that a column packed with the obtained material enables convective cation‐exchange chromatography of proteins, exhibiting flow rate independent resolution and dynamic binding capacity (8 mg mL −1 ). These flow characteristics are similar to those of monoliths and membranes and therefore improve the mass transport of existing chromatography resins used in the downstream process of therapeutic proteins, while the positive aspects of chromatographic beads are maintained, facilitating implementation in well‐developed platform technologies. Abstract : Alkyne‐terminated polyelectrolytic brushes based on 3‐sulfopropyl methacrylate are synthesized by reversible addition–fragmentation chain transfer polymerization and subsequently linked to a macroporous polymer scaffold via click chemistry. Thereby, a material is obtained that allows convective protein chromatography enabling both flow‐rate independent dynamic binding capacities and resolution.